INDUSTRI KEUANGAN BANK SYARIAH NASIONAL DALAM MASYARAKAT EKONOMI ASEAN - DEDI ISKAMTO (Universitas Islam Negeri Imam Bonjol Padang, 2016)
This paper aims to examine the position of the National Islamic banking in the ASEAN Economic Community. ASEAN Economic Community (AEC) which started in 2015 is a challenge for activists industry sharia economy. Industrial age who are not young, it should be ready to meet the sharia economic industry single market in Southeast Asia in 2015. Islamic banking, which proved resistant to crises, in particular in 1998, became the capital to face free competition in the region. ASEAN Economic Community (AEC) is a certainty that will be faced by the entire people of Indonesia and the need to anticipate that business people Indonesia not just be a spectator but also players who take advantage of the MEA. After going through a SWOT analysis of the current condition of Indonesia is in the Defensive Cells 4. Cell 4 is the most unfavorable situation. Companies facing major environmental threat, interim relatively weak position. This situation clearly requires strategies that fix involvement in product or market that can be studied.